2012
DOI: 10.1103/physrevb.85.201409
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced preferential dehydrogenation of graphane

Abstract: We have used first-principles simulations based on time-dependent density functional theory to show that short laser pulses can trigger preferential hydrogen desorption from the upper or lower side of suspended graphane (H-terminated graphene). This control is achieved by using intense ultrashort p-polarized laser pulses (∼2 fs) with an asymmetric time envelope. The dynamical Stark effect induced by the pulse creates an asymmetric charge distribution and force field on the H ions, even at low laser fluence. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Upon excitation with ns pulses e−h recombination occurs during the pulse and heat reduction of GO dominates. It should be noted that the threshold fluence required to reduce the sheet resistance in our experiments, 3.5 mJ cm −2 (corresponding to 1 mW output power), is close to the recently predicted theoretical value for non‐thermal removal of oxygen atoms from the GO lattice 48…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Upon excitation with ns pulses e−h recombination occurs during the pulse and heat reduction of GO dominates. It should be noted that the threshold fluence required to reduce the sheet resistance in our experiments, 3.5 mJ cm −2 (corresponding to 1 mW output power), is close to the recently predicted theoretical value for non‐thermal removal of oxygen atoms from the GO lattice 48…”
Section: Resultssupporting
confidence: 90%
“…With the progression of laser irradiation, thermal effects become more and more pronounced46 giving rise to photohermal breakage of carbon bonds, which increases the number of defects in the lattice and in turn leads to the formation of smaller and smaller crystalline graphene domains 47. It is concluded that removal of oxygen atoms from graphene sheets takes place without causing any damage to the lattice by precise tuning of the laser power and pulse number, which is consistent with recent theoretical calculations 48. The presence of non‐thermal and thermal components during the reduction process is further supported by two additional experimental findings: a) contrary to the fs case, the D/G peak intensity is rapidly and monotonically increasing upon irradiation with nanosecond (ns) laser pulses of the same incident fluence (Supporting Information Figure S5); and, b) the ablation threshold was shifted to lower fluences when the pulse repetition rate is increased from kHz to MHz (Supporting Information Figure S6) indicating cumulative effects due to successive pulses.…”
Section: Resultssupporting
confidence: 85%
“…Later, the femtosecond laser irradiation‐induced effective reduction of GO was confirmed by performing a first‐principles simulation of electron–ion dynamics based on the time‐dependent density functional theory . In the simulations, a laser shot was mimicked by an alternating electric field (E field), and electron–ion dynamics were performed for a GO sheet.…”
Section: Gos and Photoreduction Strategiesmentioning
confidence: 99%
“…Dehydrogenation of graphane is also possible under the action of short (*2 fs) laser pulses. 121 The systems thus fabricated can be represented by a GNR confined between high potential barriers originated from graphane. 51 Therefore, one can expect that the electronic properties of`nanoroads' will be similar to those of GNRs.…”
Section: Hydrogenated Graphenementioning
confidence: 99%